2019
DOI: 10.2147/ndt.s193891
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of melatonin in children with attention-deficit/hyperactivity disorder with sleep disorders after methylphenidate treatment</p>

Abstract: PurposeMethylphenidate (MPH), the first-line medication in children with attention-deficit/hyperactivity disorder (ADHD), is associated with increased risk of sleep disorders. Melatonin has both hypnotic and chronobiotic properties that influence circadian rhythm sleep disorders. This study explores the effectiveness of melatonin in children with ADHD who developed sleep problems after starting MPH.Patients and methodsThis study, based on a clinical database, included 74 children (69 males, mean age 11.6±2.2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The effects of MLT supplementation after the first weeks were comparable with those observed after 3 months [114]. Masi et al and Weiss et al found that combination therapy of MPH and MLT was effective and safe [82,113].…”
Section: Safety Of Exogenous Melatonin In Pediatric Patientsmentioning
confidence: 60%
See 3 more Smart Citations
“…The effects of MLT supplementation after the first weeks were comparable with those observed after 3 months [114]. Masi et al and Weiss et al found that combination therapy of MPH and MLT was effective and safe [82,113].…”
Section: Safety Of Exogenous Melatonin In Pediatric Patientsmentioning
confidence: 60%
“…The effects of melatonin supplementation in ASD patients are shown in [59] did not confirm the influence of exogenous melatonin on the change of awakening frequency. Moreover, in the literature, the researchers also indicate a mild hypnotic [82,91,106], chronobiotic effect and improved daily behavior [59,107].…”
Section: Melatonin In the Treatment Of Sleep Disorders In Childrenmentioning
confidence: 91%
See 2 more Smart Citations
“…56 At the same time, there have been observed benefits of NVNM dietary supplements in conjunction with medications, such as melatonin for insomnia treatment among children with attention deficit hyperactivity disorder using stimulant types of prescription medications. 57…”
Section: Discussionmentioning
confidence: 99%